Parental Perceptions of a Motivational Interviewing–Based Pediatric Obesity Prevention Intervention. (June 2013) - Woo Baidal, Jennifer A.; Price, Sarah N.; Gonzalez-Suarez, Elizabeth; Gillman, Matthew W.; Mitchell, Kathleen; Rifas-Shiman, Sheryl L.; Horan, Christine M.; Gortmaker, Steven L.; Taveras, Elsie M.
Motivational interviewing (MI) shows promise for pediatric obesity prevention, but few studies address parental perceptions of MI. The aim of this study was to identify correlates of parental perceptions of helpfulness of and satisfaction with a MI-based pediatric obesity prevention intervention. We studied 253 children 2 to 6 years of age in the intervention arm of High Five for Kids, a primary care–based randomized controlled trial. In multivariable models, parents born outside the United States (odds ratio [OR] = 8.81; 95% confidence interval [CI] = 2.44, 31.8), with lower household income (OR = 3.60; 95% CI = 1.03, 12.55), and with higher BMI (OR = 2.86; 95% CI = 1.07, 7.65) were more likely to perceive MI-based visits as helpful in improving children's obesity-related behaviors after the first year of the intervention. Parents of female (vs male), black (vs white), and Latino (vs white) children had lower intervention satisfaction. Our findings underscore the importance of tailoring pediatric obesity prevention efforts to target populations.